1994
DOI: 10.1002/jmv.1890430303
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotypes, reactivity to recombinant immunoblot assay 2 antigens and liver disease

Abstract: To clarify the relationship between hepatitis C virus (HCV) genotypes and liver disease, we typed HCV genomes in the sera of 151 blood donors, 180 patients with type C chronic liver disease (CLD), and 30 haemophiliacs residing in Hiroshima, Japan. All of the subjects were positive for anti-HCV and HCV-RNA, and were examined for seroreactivity to HCV-specific antigens. The HCV genotypes were determined by polymerase chain reaction (PCR) with type-specific primers deduced from the putative core region of the HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…It seems, therefore, likely that absence of anti-NS4 in RIBA-2 is sig nificantly associated with infection by HCV types other than type 1, as has been already suggested [8,16].…”
Section: Tm Samples and Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…It seems, therefore, likely that absence of anti-NS4 in RIBA-2 is sig nificantly associated with infection by HCV types other than type 1, as has been already suggested [8,16].…”
Section: Tm Samples and Methodsmentioning
confidence: 90%
“…Several reports have shown that genotype 1 strains are associated with more severe disease than are genotypes 2 and 3 and are less responsive to the IFN therapy [5,6], thus suggesting that identification of the viral genotype infecting the patient may be relevant for prognosis and clinical man agement. At the moment, it is unclear whether the current diagnostic assays may be less efficient in detecting infec tions by HCV genotypes other than genotype 1 [7][8][9] or may perform with especial features (weak reactivities or indeter minate results) in patients infected by certain genotypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, patients with genotype 1b have a more severe and progressive liver disease [12][13][14][15] and are more likely to have a decreased likelihood of success with IFN therapy. [16][17][18][19] On the contrary, genotype 2a is more likely to be found among apparently healthy blood donors than in patients with CLD, 32 or in patients with mild CLD or in those who respond better to IFN therapy. [12][13][14][15][16][17][18][19] HCV might be a causative cofactor in the pathogenesis of B cell NHL: it is found in a significative percentage of some histotypes of NHL, 8,11,33,34 it is known to be able to infect B lymphocytes circulating in the peripheral blood (PB) 35 or infiltrating the bone marrow (BM) 36 and the liver, 37 and in vitro studies have shown its ability to infect a human BM-derived B cell line and the PB MNC from healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The HCV core peptide sequences used in this study correspond to subtype 1a, and among the Spanish blood donors, subtype 1b is highly prevalent and subtype 1a relatively infrequent [8]. Although the HCV core protein contains type-specific epitopes, type-related differences in HCV antibody patterns mainly respond to antigenic diversity in nonstructural proteins [9, 10]and lack of anticore response in individuals infected by subtype 1b has not been related to sequence diversity in the immunodominant epitopes of the core antigen [11]. It seems, therefore, very unlikely that the HCV genotype distribution among our samples affected the results obtained with the HCV core multipeptide assay.…”
Section: Discussionmentioning
confidence: 99%